Treatment of port wine stain with Tixel‐induced rapamycin delivery following pulsed dye laser application. Issue 1 (4th December 2019) - Artzi, Ofir; Mehrabi, Joseph N.; Heyman, Lee; Friedman, Or; Mashiah, Jacob
Abstract: Although pulsed dye laser (PDL) is considered the gold standard treatment for port wine stains (PWS), post PDL revascularization is one of the main causes of incomplete regression and recurrence. Recently, topical sirolimus have been shown to improve treatment outcome probably through minimizing post‐laser revascularization. We sought to evaluate the added value of the Tixel drug delivery system (DDS) to the PDL and topical rapamycin treatment for PWS. This case series includes three teenager patients with previously treated PWS with PDL. Upon enrollment, every stain was divided into A and B halves for treatment assignments to the following regimens: (A) PDL + DDS + rapamycin; (B) PDL + rapamycin. Subjects were instructed to apply rapamycin topically over the PWS twice daily for the entire treatment period. Assessment of the treatment and adverse reactions as well as photographs was performed at baseline and before every PDL treatment. There were clinically significant differences in blanching responses favoring PWS receiving PDL + DDS + rapamycin as compared to PDL + rapamycin alone. Transient hyperpigmentation was noted in one patient. Two patients developed mild transient irritation and dermatitis following the treatment on both halves. The use of drug delivery system combined with topical rapamycin has no remarkable adverse effects, improves the results of PDL treatment for port wine stains, and can reduce the total number of required PDL sessions.